Learning as Transformation in the Development of Expertise by Elite Indigenous Australian Athletes - Richard L. Light; John R. Evans (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
This article addresses the lack of attention paid to research on the development of Indigenous sporting expertise from a socio-cultural perspective. It inquires into the role that informal games played in the development of Australian Indigenous AFL and NRL players up to the age of thirteen. The study adopted a combined narrative inquiry and constructivist grounded theory methodology. The study highlighted to central role that informal games played in the development of expertise and a distinctive Aboriginal style of play shaped by Indigenous culture. This article suggests the central role that informal games shaped by Aboriginal culture played in the development of expertise and an Aboriginal style of play. It also suggests the need for coaching beyond Indigenous players to consider the use of games in training regimes.